Culture and society at Lullingstone Roman Villa - Mackenzie, Caroline K. (Archaeopress Publishing Ltd, 2019)
'Culture and Society at Lullingstone Roman Villa' paints a picture of what life might have been like for the inhabitants of the villa in the late third and fourth centuries AD. The villa today, in the Darent Valley, Kent, has an unusual amount of well-preserved evidence for its interior decoration and architecture. Seventy years on from the commencement of the excavation of the site, this study draws on the original reports but also embraces innovative approaches to examining the archaeological evidence and sheds new light on our understanding of the villa's use. For the first time, the site of Lullingstone Roman Villa is surveyed holistically, developing a plausible argument that the inhabitants used domestic space to assert their status and cultural identity